HEALTHY Intervention: Fitness, Physical Activity, and Metabolic Syndrome Results - Jago, Russell (2011)
PURPOSE: This study aimed to assess the effect of the HEALTHY intervention on the metabolic syndrome (Met-S), fitness, and physical activity levels of US middle-school students. METHODS: Cluster randomized controlled trial conducted in 42 (21 intervention) US middle schools. Participants were recruited at the start of sixth grade (2006) when baseline assessments were made, with post-assessments made 2.5 yr later at the end of eighth grade (2009). The HEALTHY intervention had four components: 1) improved school food environment, 2) physical activity and eating educational sessions, 3) social marketing, and 4) revised physical education curriculum. Met-S risk factors, 20-m shuttle run (fitness), and self-reported moderate to vigorous physical activity (MVPA) were assessed at each time point. Ethnicity and gender were self-reported. Obesity status (normal weight, overweight, or obese) was also assessed. RESULTS: At baseline, 5% of the participants were classified with Met-S, with two-thirds of the males and one-third of the females recording below average baseline fitness levels. Control group participants reported 96 min of MVPA at baseline with 103 min reported by the intervention group. There were no statistically significant (P < 0.05) differences in Met-S, fitness, or MVPA levels at the end of the study after adjustment for baseline values and confounders. There were no differences in any ethnic, obesity, or ethnic × obesity subgroups for either gender. CONCLUSIONS: The HEALTHY intervention had no effect on the Met-S, fitness, or physical activity levels. Approaches that focus on how to change physical activity, fitness, and Met-S using nonschool or perhaps in addition to school based components need to be developed.